CASP5 associated with PANoptosis promotes tumorigenesis and progression of clear cell renal cell carcinoma - Kangkang Yang; Yushuang Wang; Yuli Jian; Bo Wang; Hao Du; Yuqing Xia; Jianlei Bi; Meihua Guo; Zhi Li; Ning Wang (Cancer Cell International)
Abstract Clear cell renal cell carcinoma (ccRCC) is a globally severe cancer with an unfavorable prognosis. PANoptosis, a form of cell death regulated by PANoptosomes, plays a role in numerous cancer types. However, the specific roles of genes associated with PANoptosis in the development and advancement of ccRCC remain unclear. Our study developed a risk model utilizing three PANoptosis-associated genes (Caspase 4 (CASP4), TLR3, and CASP5). This model demonstrated a high degree of precision in predicting the prognosis for patients with ccRCC. ccRCC patients in the high-risk group had the strongest immune cell activity, experiencing immune evasion, and might potentially derive advantages from treatment involving combined immune checkpoint inhibitors. CASP5 was highly expressed in ccRCC tissues by RT-qPCR, western blotting, and immunofluorescence. Stable CASP5 knockdown cell lines were constructed by lentivirus in vitro transfection technique. Reducing CASP5 level suppressed the growth, migration, and invasion of ccRCC cells, while encouraging cell apoptosis. In addition, the results of in vivo tumorigenesis experiments showed that down-regulating CASP5 expression inhibited the tumorigenic ability of 786-O cells. Together, the innovative risk model using PANoptosis-associated genes effectively forecasts the tumor microenvironment and survival rates for ccRCC, offering a novel approach to the early, precise diagnosis of ccRCC and the advancement of personalized treatment strategies.